STRATEGI PENGAJARAN MEMBACA UNTUK SISWA DENGAN KESULITAN BELAJAR DI SEKOLAH DASAR - Emilia Safitri; Syena Auly Amelia; Desty Endrawati Subroto (Jurnal Padamu Negeri, 2025)
This study aims to identify and design efficient reading teaching approaches for children in elementary schools who experience learning difficulties. Children with learning difficulties often find it difficult to understand and digest written information, so they need learning methods that can be adapted to their individual needs. The method used in this research is a qualitative approach with a focus on descriptive case studies, as well as observations and interviews. The findings from this research indicate that teacher support through constructive feedback, strengthening motivation, and parental involvement plays an important role in helping the development of reading skills. This research suggests implementing organized, adaptive, and student-focused learning methods to create inclusive and effective learning experiences. In this way, students who face learning difficulties can make significant progress in their reading abilities.